An algorithmic framework for hybrid adaptive protocol (HAP) to manage broadcast storm problems in mobile ad-hoc networks (MANETS) (2008)
The consequences of pure flooding which is amongst the simplest and the most straight forward approach to performing broadcast include redundant broadcast, contention and collision which are collectively referred to as broadcast storm problem (BSP). This is as a result of the use of plain broadcasting approaches leading to signal overlap in a geographical area with wireless communication. The Counter-based scheme was developed to reduce Broadcast Storm problem. However, to be able to maintain high delivery ratio in either a sparse or dense networks, different thresholds are required. Because of the nature of MANETs determining this threshold require a level of dynamism, without which its operation will be marred. This research work thus proposed an algorithmic framework to address the BSP problem, using the knowledge of it neighbourhood density to dynamically determine the threshold so as to adapt to both dense and sparse network while limiting the above stated constrains.